Analisis Faktor Kesulitan Mahasiswa Dalam Menyelesaikan Nilai Gagal Menggunakan Metode Algoritma C4.5 - ELa Roza Batubara; Zakarias Situmorang (Jurnal Dinamika Informatika, 2022)
The purpose of this study was to determine the most dominant factor in students' difficulties in completing failed grades. In this study, researchers used Data Mining techniques using the C4.5 algorithm. Sources of research data used were obtained from interviews and giving questionnaires to students at random in the AMIK Tunas Bangsa Pematangsiantar environment. The research variables used are the costs incurred (C1), time taken (C2), motivation to try to work (C3), student awareness (C4), and information obtained (C5). In this study, the alternative used as a sample was AMIK Tunas Bangsa students, sixth semester. The results of the classification using the C4.5 algorithm and testing with rapidminer software found that the most dominant factor in the difficulty of students completing the failed score was the cost incurred (C1) with a gain value of 0.15577244.